2006
DOI: 10.1002/ajmg.b.30432
|View full text |Cite
|
Sign up to set email alerts
|

HTR2C and HTR1A gene variants in German and Italian suicide attempters and completers

Abstract: The serotonin 2C (HTR2C) and 1A (HTR1A) receptors have been involved in suicide-related behaviors. We studied gene variants of both receptors in suicide attempters and completers. The sample was composed of 167 German suicide attempters (affective spectrum n = 107, schizophrenia spectrum n = 35, borderline personality disorder n = 25), 92 Caucasian individuals who committed suicide, 312 German healthy subjects, 152 Italian suicide attempters (major depression n = 68 and bipolar disorder n = 84), and 131 Italia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 58 publications
3
45
3
3
Order By: Relevance
“…A brain imaging study also found that the G allele and 5-HT1A receptor binding increases in both the raphe nuclei and other brain regions [19]. Therefore, this could cause a greater extent of desensitization of 5-HT1A auto receptors, reduce raphe firing, decrease serotonin release, and confer resistance to SSRIs [20,21]. In contrast, in cells expressing 5-HT1A post synoptically, Deaf-1 activity is opposed in presynaptic versus postsynaptic neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A brain imaging study also found that the G allele and 5-HT1A receptor binding increases in both the raphe nuclei and other brain regions [19]. Therefore, this could cause a greater extent of desensitization of 5-HT1A auto receptors, reduce raphe firing, decrease serotonin release, and confer resistance to SSRIs [20,21]. In contrast, in cells expressing 5-HT1A post synoptically, Deaf-1 activity is opposed in presynaptic versus postsynaptic neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in cells expressing 5-HT1A post synoptically, Deaf-1 activity is opposed in presynaptic versus postsynaptic neuronal cells. Thus, Deaf-1 activates 5-HT1A transcription by binding to the C allele but not the G allele [20,21]. Therefore, the G-1019 allele might reduce Deaf-1-enhanced postsynaptic 5-HT1A transcription as well as enhance resistance to antidepressant-induced increases in 5-HT [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Por lo que se ha establecido la asociación del alelo s de este polimorfismo con desordenes cono la ansiedad, depresión y conducta suicida (Lesch et al, 1996;Mann et al, 2000;Pungercic et al, 2006). Un reciente Meta-análisis que analiza a 44 estudios reporto que portadores del alelo corto de este polimorfismo presentan mayor riesgo de conducta suicida (Serretti et al, 2007).…”
Section: Genes Candidatos De La Conducta Suicidaunclassified
“…Variaciones genéticas en el receptor de serotonina 5-HT2A se asocia con la conducta suicida. La mayoría de los estudios que analizan la posible asociación del polimorfismo C102T y la conducta suicida observan un exceso del genotipo C/C en los pacientes con intentos suicidas (Nishiguchi et al, 2002;Ohtani, Shindo, & Yoshioka, 2004;Serretti et al, 2007). Sin embargo los resultados son inconsistentes (Hung et al, 2011;Murphy et al, 2011;Preuss, Koller, Bahlmann, Soyka, & Bondy, 2000).…”
Section: Receptores a Serotoninaunclassified
See 1 more Smart Citation